Flexible TiO2 nanograss array film decorated with BiOI nanoflakes and its greatly boosted photocatalytic activity. Issue 6 (15th March 2021) - Hao, Liang; Hu, Yifei; Zhang, Yan; Ping, Xuecheng; Liu, Tongyang; Zhao, Qian; Lu, Yun; Liu, Jizi
Abstract: A flexible TiO2 nanograss array film on Ti wire mesh was prepared by a mild chemical reaction. To overcome its shortcoming of almost no absorption of visible light, successive ionic layer adsorption and reaction (SILAR) was executed to decorate the prepared TiO2 film with BiOI. The results of XRD and SEM measurements showed that BiOI nanoflakes formed on the surface of TiO2 film, and the loading amounts of BiOI nanoflakes increased with the increase in SILAR cycles. The XPS results confirmed the heterojunction formation of BiOI-TiO2 . The photocurrent measurement suggests that a moderate loading amount of BiOI nanoflakes is beneficial to improve the charge separation efficiency, which is ascribed to the heterojunction formation of BiOI-TiO2 . The BiOI-decorated TiO2 film with SILAR cycles of seven showed the most excellent visible-light photocatalytic activity among all the samples. Compared with the bareTiO2 nanograss array film, its visible-light photocatalytic activity increased by 11.7 times. The flexible BiOI-decorated TiO2 nanograss array film with high photocatalytic activity shows great applications in air pollution and the pollution caused by offshore oil spills.